The role of cell plasticity in progression and reversal of renal fibrosis - Dussaule, Jean-Claude (Blackwell Publishing Ltd, 2011)
The need for novel insights into the mechanisms of progression of renal disease has become urgent during the last several years because of the increasing incidence of chronic renal disease worldwide. Independent of the underlying disease, the subsequent progression of renal fibrosis is characterized mainly by both an exaggerated synthesis and abnormal accumulation of extracellular matrix proteins produced by mesenchymal cells within the kidney. These cells are mainly myofibroblasts deriving from a variety of renal cells such as vascular smooth muscle, mesangial, resident stem, tubular epithelial, vascular endothelial cells or pericytes. The appearance of myofibroblasts is a reversible process, as suggested by studies in experimental models showing regression of renal fibrosis during therapy with antagonists and/or blockers of the renin–angiotensin system. An additional factor that can also affect the mechanisms of progression/regression of fibrosis is the plasticity of podocytes controlling glomerular filtration.